2022
DOI: 10.37896/ymer21.05/33
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mulligan Bent Leg Raise Technique on Low Back Pain Subjects with Radiculopathy

Abstract: Brain Mulligan pioneered the use of manual therapy techniques. In clinical practise, these approaches are often utilised. Among many techniques, bent leg raise is an innovative technique that is said to improve the range of straight leg raise, reduce pain, and reduce the degree of impairment in low back pain with radiculopathy. Clinical trial has not sufficiently demonstrated the efficacy of this approach. As a result, research on the effectiveness of the bent leg raise approach in low back pain with radiculop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…Twelve trials 24 35 with a total of 432 participants evaluated the impact of hamstring stretching on pain intensity using a VAS and NPRS. Hamstring stretching resulted in lower pain scores compared to regular treatment in different categories of LBP (SMD = −0.72, 95% CI: −1.35 to −0.09; I 2 = 89%, p = 0.03).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twelve trials 24 35 with a total of 432 participants evaluated the impact of hamstring stretching on pain intensity using a VAS and NPRS. Hamstring stretching resulted in lower pain scores compared to regular treatment in different categories of LBP (SMD = −0.72, 95% CI: −1.35 to −0.09; I 2 = 89%, p = 0.03).…”
Section: Resultsmentioning
confidence: 99%
“…Six trials 24 , 32 34 , 36 , 37 involving a total of 225 participants evaluated the impact of hamstring stretching on hamstring muscle flexibility. Subgroup analysis showed that hamstring stretching resulted in a greater range of motion for hamstring muscle flexibility compared to regular treatment specifically for cases of back pain with radiating pain (SMD = 2.39, 95% CI: 1.76–3.02; I 2 = 0%, p < 0.001).…”
Section: Resultsmentioning
confidence: 99%
“…These techniques are administered while patients engage in either active or passive movements or during resisted muscle contractions. Mulligan's approach is conducted within the pain-free range of motion, potentially enhancing its safety compared to other manual therapy methods [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…These techniques are administered while patients engage in either active or passive movements or during resisted muscle contractions. Mulligan's approach is conducted within the pain-free range of motion, potentially enhancing its safety compared to other manual therapy methods [13]. suggested that the prompt pain-relieving effects of Mulligan's techniques could be attributed to the activation of non-opioid endogenous pain inhibition pathways.…”
Section: Discussionmentioning
confidence: 99%
“…It is fairly simple to observe how each component contributes to or keeps the cycle of harm going as we go around it. (27) (28) Maintaining hamstring muscle flexibility is important for the general and athletic population, as well as for health care professionals. To achieve this goal, one must first learn the most effective and efficient technique for gaining hamstring flexibility.…”
Section: Discussionmentioning
confidence: 99%